Optimasi Penggunaan Pondasi Micropile sebagai Pondasi Mesin Turbin: Studi Kasus Pabrik Gula Candi Baru Sidoarjo - Muhammad Rusydan; Agus Tugas; Abdul Halim (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
The foundation of turbine machines in industrial buildings must be able to withstand static and dynamic loads caused by operational vibrations. Generally, reinforced concrete block foundations are used due to their good stability. However, under certain conditions such as limited land, decreased soil bearing capacity, and the need for structural rehabilitation, their application becomes less effective. Therefore, this study aims to analyze the use of Micropile foundations as an alternative for turbine machine foundations at Candi Baru Sugar Factory, Sidoarjo.The research method includes literature studies, soil data collection through Cone Penetration Test (CPT), machine technical data analysis, and the design and analysis of Micropile foundations. The analysis covers bearing capacity, settlement, dynamic response, pile cap design, and cost estimation.The results indicate that Micropiles with a diameter of 0.20 m, a length of 2 m, five piles, and a pile cap size of 2 m × 2 m × 4.5 m are able to safely and stably support the machine load. In addition, this system is considered more efficient in terms of construction time and implementation. Therefore, Micropile foundations are recommended as an effective and economical alternative for turbine machine foundations.